UNIFICATION OF OVERHEAD LINES IN THE CONDITIONS OF THE MARKET OF TWO-PARTY AGREEMENTS AND BALANCING ELECTRIC ENERGY MARKET - Lezhnuik, Petro; Cheremisin, Mykola; Cherkashina, Veronika (Scientific Works of Vinnytsia National Technical University, 2015)
The paper considers one of the trends in the development of electric transmission overhead lines in the conditions of the market of two-party agreements and balancing electric energy market: optimization of the parametric series of wire cross-sections. REFERENCES 1. Закон України про засади функціонування ринку електричної енергії України [Електронний ресурс // Режим доступу : ]http://zakon4.rada.gov.ua/laws/show/663-18. 2. Кириленко О. В. Балансуючий ринок електроенергії і його математична модель / О. В. Кириленко, І. В. Блінов, Є. В Парус // Технічна електродинаміка. – 2011. – № 2. – С. 36 – 43. 3. Энергетическая стратегия России на период до 2030 г. [Электронный ресурс] // Режим доступа: http://minenergo.gov.ru/aboutminen/energostrategy/. 4. Правила устройства электроустановок. // Х.: Изд-во «Форт», 2009. – 704 с. 5. Будзко И. А. Унификация воздушных линий электропередечи / И. А. Будзко, Ю. Н. Астахов, Н. М. Черемисин // Электричество. – 1982. – № 2. – С. 1 – 11. 6. Файбисович Д. Л. Предложения по унификации сечений проводов воздушных линий напряжением 110 – 750 кВ / Д. Л. Файбисович // Энергетик. – 2003. – № 3. – С. 21 – 22. 7. Выбор приоритетного направления в проектировании воздушных линий электропередачи в условиях рыночных отношений / Н. М. Черемисин, В. В. Черкашина // Сборник трудов VI Всероссийской научно- технической конференции с международным участием “Энергетика: управление, качество и эффективность использования энергоресурсов”. – Россия. Благовещенск: АГУ – 2011. –Т.1.– С. 105 – 110.